Implementasi Program Kampus Mengajar Angkatan 2 di Kabupaten Karawang) - Arum Sari; Eka Yulyana; Mochamad Faizal Rizki (Peneliti.net, 2022)
Elementary school (SD) is the most basic level of formal education in Indonesia. Elementary school is taken in 6 years, starting from grade 1 to grade 6. Teaching Campus Batch 2 of 2021 is part of the Merdeka Learning Campus Merdeka (MBKM) program launched by the Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud) and supported by the Fund Management Institute. Ministry of Finance Education (LPDP) which opens opportunities for students to become educators in Elementary Schools (SD) in the 3T (front, behind and outermost) areas to assist learning during the pandemic, by presenting students as part of strengthening literacy and numeracy learning where students become partners teachers in carrying out creativity and innovation in learning. The assignment of service programs for students who pass the selection in the field starts from August 4 – December 17, 2021.